Parking Slot Reservation System for Efficient Resource Utilization and Profit - et. al., Kanaga Suba Raja.S , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Theparkingspacesavailableindaily moving lifestyle is not considered for parking. This problem causes many people to park their vehicles road side and results traffic violations and many accidents in major cities. These can be avoided when people can find the available parking spaces and reserve them to park their vehicles before reaching to that specific area. The main idea is based on mobile applications where the client and the vendor uses mobile applications for their purposes. The client can viewavailableparkingareasintheirdestination and can book them in advance before reaching them. The vendor application can be used by the parking lot owners to authenticate the incoming vehicles and allocate slots for both the client booked with application and naive users coming without using client application. The main algorithms used provides profit to both the users and the parking lot owners and best slot allocation algorithm. By this way many unused and distance parking lots can be utilisedinordertoreducetheroadsideparkings